EVALUASI PENERAPAN GOOD CORPORATE GOVERNANCE PADA BANK PD BPR SARIMADU - Sundari, Hastrid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
This research is to see the application of the principles ofgood corporate governance in banks PD BPR Sarimadu, to investigatethis issue, this research is using a descriptive method with aqualitative paradigm, while the data source are the primary data andsecondary data. The sample was PD BPR Sarimadu. The results ofthis study demonstrate that PD BPR Bank Sarimadu are trying tocreate a business climate that is clean and healthy by trying tosuppress the behavior of fraud on lending procedures that wereimplemented in the company by applying the principles of goodcorporate governance in the company's activities. From this study itcan be concluded that there are an effect from applying the principlesof good corporate governance on corporate performance. Since it firstapplied, this principles of good corporate governance so far managedto reduce the level of credit risk with a decreasing trend.